Implementation of a real time Microgrid Management System for Photovoltaic based Distributed Generation systems - Bayrak, Gokay; Gencoglu, Muhsin Tunay; Cebeci, Mehmet (Crc Press-Balkema, 2015)
This study focuses on developing a real time Microgrid Management System (MGMS) for Photovoltaic (PV) based Distributed Generation (DG) systems. In the study, a 1 kWp installed power grid tied PV system is set up in the laboratory. The developed PV system to perform the MGMS consists of a PV array, a DC/DC converter, a grid tied PV inverter and the load. The Electronic Measurement Circuits (EMCs) are designed to measure current, voltage, power, phase angle etc. at the PV inverter output side, at the load side and the grid side. The obtained data from EMCs is transmitted to a Data Acquisition (DAQ) card in real time, and the PV system is managed thanks to the implemented Labview based MGMS. All the parameters of the PV system could be monitored by the MGMS, and this structure also allows the users controlling the power flow with controlling the circuit breakers which are set up on the three sides of the PV system. The obtained experimental results are indicated in the paper, and it is clear that the proposed system is fast, reliable, low cost and it could be easily implemented for PV based DG systems. On the other hand, the proposed MGMS is suitable for real time applications, and it could be adapted easily to the other DG systems.
International Conference on Biotechnology, Agriculture, Environment and Energy (ICBAEE) -- MAY 22-23, 2014 -- Beijing, PEOPLES R CHINA
Keywords: photovoltaic; microgrid; microgrid management; distributed generation; data acquisition